On the Structure of Structure-Oriented Editors for Different Applications - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the ACM SIGSOFT/SIGPLAN Software Engineering Symposium on Practical Software Development Environments, Palo Alto, USA)

Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

A Time-Space Tradeoff for Element Distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (SIAM Journal on Computing)

The Complexity of Parallel Sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (SIAM Journal on Computing)

Digital Rectification Method for Radar Images Applied on Huge Arrays - Domik, Gitta (Proceedings of the First Int'l. Workshop on Image Rectification Tech. for Spaceborne Synthetic Aperture Radar)

Methods and application of surface shape reconstruction from multiple SAR images - Domik, Gitta (IGARSS'87-International Geoscience and Remote Sensing Symposium)

Methods and accuracy of operational digital image mapping with aircraft SAR - Leberl, Franz; Domik, Gitta; Mercer, Bryan J (1987 ASPRS ACSM Annual Convention)

Classes of first order formulas under various satisfiability definitions - Kleine Büning, H.; Lettmann, Theodor (8th International Conference on Automated Deduction)

Multiple incidence angle SIR-B experiment over Argentina: generation of secondary image products - Domik, Gitta; Leberl, Franz; Cimino, Jobea (IEEE Transactions on Geoscience and Remote Sensing)

Digital terrain mapping with STAR-1 SAR data - Mercer, JB; Lowry, RT; Leberl, Franz; Domik, Gitta (International Geoscience and Remote Sensing Symposium)

Developing tools for digital radar image data evaluation - Domik, Gitta; Leberl, Franz; Raggam, J (Remote sensing for resources development and environmental management; Proceedings of the Seventh International Symposium)

On the Structure of an Incremental and Integrated Software Development Environment - Engels, Gregor; Lewerentz, Claus; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the 19th Hawaii International Conference on System Sciences, Hawaii, USA)

Experiences with a Hybrid-Interpreter Based on Incremental Compilation Techniques - Engels, Gregor; Sandbrink, Andrea (Proceedings of the Workshop on Compiler Compilers and Incremental Compilation Techniques, Bautzen)

Graphen als zentrale Datenstrukturen in einer Software-Entwicklungsumgebung - Engels, Gregor

Efficient Simulations among Several Models of Parallel Computers - Meyer auf der Heide, Friedhelm (SIAM Journal on Computing)

A tradeoff between search and update time for the implicit dictionary problem - Borodin, Allan; Fich, Faith E.; Meyer auf der Heide, Friedhelm; Upfal, Eli; Wigderson, Avi (Automata, Languages and Programming)

Speeding up random access machines by few processors - Meyer auf der Heide, Friedhelm (STACS 86)

A time-space tradeoff for element distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (STACS 86)

Radar Stereomapping Techniques and Application to SIR-B Images of Mt. Shasta - Leberl, F.; Domik, Gitta; Raggam, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

Multiple Incidence Angle SIR-B Expenment Over Argentina: Stereo-Radargrammetrc Analysis - Leberl, F.; Domik, Gitta; Raggam, J.; Cimino, J.; Kobrick, M. (IEEE Transactions on Geoscience and Remote Sensing)

Using secondary image products to aid in understanding and interpretation of radar imagery - Domik, Gitta; Leberl, Franz (IGARSS'86: Remote Sensing: Today's Solutions for Tomorrow's Information Needs)

Radargrammetric Experiments with Space Shuttle SIR-B Imagery - Leberl, Franz; Domik, Gitta; Raggam, J; Cimino, J; Kobrick, M (International archives of photogrammetry and remote sensing= Archives internationales de photogrammétrie et de télédétection= Internationales Archiv der Photogrammetrie und Fernerkundung)

Radar image simulation as a tool to analyze topographic effects on geometry and radiometry of radar imagery - Domik, Gitta (Machine processing of remotely sensed data- Quantifying global process: Models, sensor systems, and analytical methods)

Radargrammetric aspects of SAR data evaluation - Raggam, J; Triebnig, Gerhard; Buchroithner, MF; Domik, Gitta; Leberl, Franz (Thematic Applications of SAR data)

Graph Grammar Engineering: A Method Used for the Development of an Integrated Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Joint Conference on Theory and Practice of Software Development (TAPSOFT 1985), Berlin (Germany))
We introduce a method to specify the functional behaviour of software tools in an incremental and integrated software development environment. This specification method is based on graph grammars. It is an adequate method to specify the behaviour of all software systems using graphs as internal data structures. We show that a specification can be developed systematically by which the adaptability of the environment is increased towards modification of tools or extension by new tools. Furthermore, guidelines for the implementation can directly be derived from this specification.

The Design of an Adaptive and Portable Programming Support Environment - Engels, Gregor; Schäfer, Wilhelm (Proceedings of the International Computing Symposium, Amsterdam (The Netherlands))

Lower time bounds for integer programming with two variables - Lautemann, Clemens; Meyer auf der Heide, Friedhelm (Information Processing Letters)

Lower bounds for solving linear diophantine equations on random access machines - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

Simulating probabilistic by deterministic algebraic computation trees - Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

The complexity of parallel sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

One, two, three . . . infinity: lower bounds for parallel computation - Fich, F E; Meyer auf der Heide, Friedhelm; Ragde, P; Wigderson, A (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Fast algorithms for n-dimensional restrictions of hard problems - Meyer auf der Heide, Friedhelm (Proceedings of the seventeenth annual ACM symposium on Theory of computing - STOC '85)

Nondeterministic versus probabilistic linear search algorithms - Meyer auf der Heide, Friedhelm (26th Annual Symposium on Foundations of Computer Science (sfcs 1985))

Lower time bounds for solving linear diophantine equations on several parallel computational models - Meyer auf der Heide, Friedhelm (Information and Control)

Mapping with aircraft and satellite radar images - Leberl, FW; Kobrick, M; Domik, Gitta (The Photogrammetric Record)

Towards a SAR system for snow and land ice applications - Rott, H; Domik, Gitta; Mätzler, C; Miller, H (ESA Proceedings of a Workshop on Thematic Applications of SAR DATA p 29-39(SEE N 86-28488 19-42))

Radar Image Simulation and its Application in Image Analysis - Domik, Gitta; Leberl, F.; Kobrick, M. (International archives of photogrammetry and remote sensing)

Rectification of Radar Images Using Stereo- Derived Height Models and Simulations - Domik, Gitta; Leberl, F.; Raggam, J. (XVth Congress of the International Society for Photogrammetry and Remote Sensing)

Evaluation of radar stereo viewability by means of a simulation technique - Domik, Gitta (ESA IGARSS 84: Remote Sensing: From Res. towards Operational Use,)

A Polynomial Linear Search Algorithm forr the n-Dimensional Knapsack Problem - Meyer auf der Heide, Friedhelm (Journal of the ACM (JACM))

On The Limits To Speed Up Parallel Machines By Large Hardware And Unbounded Communication - Meyer auf der Heide, Friedhelm; Reischuk, R. (25th Annual Symposium onFoundations of Computer Science, 1984.)

Efficient simulations among several models of parallel computers (extended abstract) - Meyer auf der Heide, Friedhelm (STACS 84)

Method to Relate Digital SAR Images and Map Information in Mountainous Areas - Domik, Gitta; Kienegger, E. (Proceedings of the World Conference on Remote Sensing)

The SAR-580 experiment on snow and glaciers at the Austrian test site - Rott, H.; Domik, Gitta (Proc. SAR-580 Investigators Workshop)

Differential Rectification of SLR-Images Using Map-Derived and Radar-Generated Digital Elevation Models. - Domik, Gitta; Leberl, Franz; Raggam, Johannes

Analyse von Radarbildern mittels digitaler Hoehenmodelle - Domik, Gitta; Kobrick, M; Leberl, Franz (Bildmessung und luftbildwesen)

Software Specification by Graph Grammars - Nagl, Manfred; Engels, Gregor; Gall, Rupert; Schäfer, Wilhelm (Proceedings of the 2nd International Workshop on Graph-Grammars and Their Application to Computer Science, Osnabrück (Germany))
The following paper demonstrates that programmed sequential graph grammars can be used in a systematic proceeding to specify the changes of high level intermediate data structures arising in a programming support environment, in which all tools work in an incremental and syntax-driven mode. In this paper we lay stress upon the way to get the specification rather than on the result of this process. Therefore, we give here some approach to specification engineering using graph grammars. This approach is influenced by the syntactical definition of the underlying programming language or module concept etc. to be supported but also by the idea of the user interface.

Software Specification Using Graph Grammars - Engels, Gregor; Gall, Rupert; Nagl, Manfred; Schäfer, Wilhelm (Computing)
The following paper,demonstrates that programmed sequential graph grammars can be used in a systematic proceeding to specify tbe changes of high level intermediate data structures arising in a programming support environment, in which all tools work in an incremental and syntax-driven mode. In this paper we lay stress upon the way to get the specification rather than on the result of this process. Therefore, we give here some approach to "specification engineering" using graph grammars. This approach is influenced by the syntactical definition of the underlying language for Programming in the Small, the module concept etc. to be supported on one side but also by the idea of the user interface.

An Operational Semantics for Specifications of Abstract Data Types with Error Handling - Engels, Gregor; Pletat, Udo; Ehrich, Hans-Dietrich (Acta Informatica)
A new approach to an operational treatment of errors and exceptions in specifications of abstract data types is presented. Considering a specification as a term rewriting system, we define an operational semantics and give conditions that are sufficient for its well-definedness (Church-Rosser property). Also, we give conditions that are sufficient for the termination of reduction strategies, respecting the specified error and exception handling.

Efficiency of universal parallel computers - Meyer auf der Heide, Friedhelm (Acta Informatica)